2015
DOI: 10.5152/anatoljcardiol.2015.5961
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of late gadolinium enhancement in the assessment of acute cellular rejection after heart transplantation

Abstract: Objective:Allograft rejection is still an important cause of morbidity and mortality after heart transplantation (HTx). Many techniques in cardiac magnetic resonance imaging (CMR) were investigated to diagnose acute cellular rejection (ACR). However, there is not enough information about late gadolinium enhancement (LGE) in the myocardium and ACR.Methods:We prospectively analyzed our consecutive 41 heart transplant recipients who were admitted for routine endomyocardial biopsies. CMR was performed maximum 6 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…Conversely, a small CMR study using T2-weighted signal intensities and native T1 times, extracellular volumes, and LGE did not reliably identify acute cellular rejection in children [52]. However, the study was likely underpowered to detect the outcome.…”
Section: Cmr Imagingmentioning
confidence: 90%
See 1 more Smart Citation
“…Conversely, a small CMR study using T2-weighted signal intensities and native T1 times, extracellular volumes, and LGE did not reliably identify acute cellular rejection in children [52]. However, the study was likely underpowered to detect the outcome.…”
Section: Cmr Imagingmentioning
confidence: 90%
“…In another study by Hussain et al, 26 pediatric HT recipients underwent CTCA, IVUS, and stress CMR with tissue characterization, which showed that increasing T2 values were associated with worsening LV function and increasing T1/ECV and T2 values were associated with rejection burden and low-grade CAV [51]. However, LGE in adult HT recipients was not found to correlate with acute cellular rejection [52]. CMR imaging with quantitative T2 mapping offers a potential noninvasive method for screening pediatric HT patients for acute allograft rejection [53,54].…”
Section: Cmr Imagingmentioning
confidence: 99%
“…Az ambuláns kontrollvizsgálat során végzett echokardiográfiás vizsgálat mindhárom beteg esetén csökkent bal kamra szisztolés funkciót írt le, amely hátterében akut rejekció gyanúja (16)(17)(18)(19)(20). A 2010-es ISHLT konszenzus konferencia előtt a biopszia negatív rejekciós betegek aránya 10-20% között mozgott, ami az AMR diagnosztikájának bevezetése után csökkent (21), de továbbra sem elhanyagolható mértékű.…”
Section: Saját Tapasztalataink a Városmajori Szív-és éRgyógyászati Klunclassified
“…A szívtranszplantált betegeknél megfigyelhető késői halmozás hátterében azonban az AR mellett allograft vasculopathia és reperfúziós károsodás is állhat (3). A rendelkezésünkre álló kevés irodalmi adat alapján a késői kontraszthalmozás és AR közötti viszony ellentmondásos, egyes cikkek nem találtak korrelációt a rejekció jelenléte és súlyossága, valamint a késői halmozás megléte között (3,14,19). Ezzel szemben Butler és munkatársai a HTX-betegek utánkövetése során a miokardiális heg jelenlétét a kardiovaszkuláris halálozás és hospitalizáció független prediktorának találták (39).…”
Section: T 1 -Súlyozott Mérésekunclassified
“…Because ACR can be asymptomatic, its early detection requires active monitoring with serial endomyocardial biopsy (EMB), the gold standard for its diagnosis (7,8). However, this invasive approach poses a challenge because of its high cost and risk of complications such as RV perforation, cardiac tamponade, arrhythmia, pneumothorax, and tricuspid valve injury (3,(9)(10)(11). The currently accepted rejection classification after HT was proposed by the International Society of Heart and Lung Transplant (ISHLT) (12,13).…”
Section: ' Introductionmentioning
confidence: 99%